Intravascular ultrasound‐guided cutting balloon angioplasty for renal artery stent restenosis - Otah, Kenneth E. (Clin Cardiol, 2006)
Renal artery stenting is the procedure of choice for treating atherosclerotic renal artery stenosis; it improves the acute results of percutaneous balloon angioplasty and has a better long‐term outcome, particularly a reduced risk of restenosis. However, the treatment of renal artery stent restenosis is not well established and it is challenging because of limited therapeutic options. A novel technique of treating renal artery stent restenosis using cutting balloon angioplasty guided by intravascular ultrasound is presented.